The Influence of Service Quality, Product Quality and Word of Mouth on Nadheera Luxury Purchasing Decisions - Nisrina, Nada Putri (Economics and Business International Conference Proceeding, 2024)
This research aims to analyze the influence of service quality, product quality and word of mouth on purchasing decisions for Nadheera Luxury. The sampling technique used in this research is accidental sampling. The sample used in this research was 100 respondents. This research uses multiple linear regression analysis techniques with SPSS version 23 statistical tools. The results of this research show that service quality has a positive and significant effect on purchasing decisions, product quality has a positive and significant effect on purchasing decisions and word of mouth does not have a significant effect on purchasing decisions. . Viewed from the side, simultaneous testing, service quality, product quality and word of mouth simultaneously influence the decision to purchase Nadheera Luxury. The results of this research underline the importance of improving service and product quality for the Nadheera Luxury company in influencing consumer purchasing decisions. Even though word of mouth does not have a significant influence individually, it still has an important role in simultaneous influence. Thus, companies are expected to continue to improve the quality of services and products and consider effective promotional strategies to increase word of mouth.